PENGARUH ARUS KAS OPERASI DAN NET INCOME TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI LQ45 TAHUN 2016-2019 - Nathania, Jennifer (Media Akuntansi dan Perpajakan Indonesia, 2021)
This study aims to examine: (1) the effect of operating cash flow on stock returns in 2016-2019, (2) the effect of accounting profit or net income on stock returns in 2016-2019. The data in this study is secondary data obtained from the annual reports of companies listed in the LQ-45 stock index in the 2016-2019 period. This type of research is descriptive quantitative research. This study was conducted using a sample of 45 LQ-45 companies listed on the Indonesia Stock Exchange during the 2020 period whose data were drawn from 2016 to 2019, so that the research data analyzed amounted to 180. The data analysis technique used was descriptive statistics, classical assumption test. , multiple linear regression test. Based on the proposed test using the t test, the key is that operating cash flow has no effect on stock returns and accounting profit or net income has no effect on stock returns. Based on F Say that Operating Cash Flow and Accounting Profit simultaneously affect Stock Return.